Hellenistic Prince | Portrait statue
Derives from famous statue by Lysippus of Alexander the Great. Possibly a representation of Attalus II, king of Pergamon, or a Roman wishing to be represented as an Hellenistic prince. Shaft is a modern replica of original spear.